Exploring Visualization Models To Elucidate Learning Capacities In The Context Of Visual Hermeneutics: A Case Study Of Online Instructional Animation - Lucas, Terry; Abdul Rahim, Ruslan (2016)
Online learning is becoming more prevalent throughout the years. At the same time, learners are using various technological devices to learn via the internet. One of the common ways of online learning is by watching videos from streaming sites such as YouTube. Some educational videos that are available online are presented in a form of instructional or expository animations. With the rise of instructional animations use for learning, it is essential to identify design characteristics of such animations. Hence, this paper focuses on the visual hermeneutic study of design characteristics of instructional and expository animations available on online streaming sites. Animation samples of the study are selected from established educational animation content creators on YouTube using several criterions. Aspects such as design characteristics and visual representations will be analysed and discussed in relation to the Cognitive Theory of Multimedia Learning principles and a characterisation system of expository animation. Based on these analyses, there are commons characteristics and uniquely different approaches to creating successful online instructional and expository animations. By being able to identify and aware of these characteristics, educators and animation designers can improve the quality of visual content and instructional design to cater to their teaching and learning needs